Two Studies of Connectedness to Parents and Suicidal Thoughts and Behavior in Children and Adolescents. Issue 2 (3rd March 2016) - Conner, Kenneth R.; Wyman, Peter; Goldston, David B.; Bossarte, Robert M.; Lu, Naiji; Kaukeinen, Kimberly; Tu, Xin M.; Houston, Rebecca J.; Lamis, Dorian A.; Chan, Grace; Bucholz, Kathleen K.; Hesselbrock, Victor M.
Abstract : We tested hypotheses that greater connectedness to parent(s) is associated with lower risk for nonlethal suicidal thoughts and behavior (STB), termed direct protective effects, and that parent connectedness serves to moderate (lower) the risk for STB associated with psychopathology including major depressive episode (MDE), termed moderating protective effects. Independent samples of children and adolescents recruited for a multicenter study of familial alcoholism were studied. Generalized estimating equation models were used that adjusted for age, sex, and youth psychopathology variables. The sample for Study 1 was assessed at baseline and about 2- and 4-year follow-ups, with baseline characteristics of n = 921, M age = 14.3 ± 1.8 years, and 51.8% female. The sample for Study 2 was assessed at baseline and about 5-year follow-up, with baseline characteristics of n = 867, M age = 12.0 ± 3.2 years, and 51.0% female. In both studies, increased perceived connectedness to father but not mother was associated with lower risk for measures of STB, consistent with direct protective effects. In Study 1, measures of parent connectedness were associated with lower risk for STB but only for youth that did not experience MDE (or alcohol use disorder), inconsistent with moderating protective effects. Study 2 showed that connectedness to fathers was associated with lower risk for suicide plans or attempts (severe STB) but not frequent thoughts of death or dying (nonsevere STB). Improved connectedness to fathers may lower risk for STB in children and adolescents, consistent with direct protective effects. Hypotheses about moderating protective effects were not supported.